2018
DOI: 10.1167/18.1.12
|View full text |Cite
|
Sign up to set email alerts
|

The edge of awareness: Mask spatial density, but not color, determines optimal temporal frequency for continuous flash suppression

Abstract: The study of how visual processing functions in the absence of visual awareness has become a major research interest in the vision-science community. One of the main sources of evidence that stimuli that do not reach conscious awareness-and are thus "invisible"-are still processed to some degree by the visual system comes from studies using continuous flash suppression (CFS). Why and how CFS works may provide more general insight into how stimuli access awareness. As spatial and temporal properties of stimuli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 97 publications
5
45
2
Order By: Relevance
“…This has been shown to be the optimal temporal frequency for suppression in other CFS studies (Drewes et al, 2018;Zhu, Drewes, & Melcher, 2016), but is actually a slower rate than Cohen et al (2015), who used ~117 ms (8.5 Hz); nevertheless we found comparable breakthrough times (see Experiment 3). A trial started with the presentation of the black fixation dot for 250 ms which then turned red for 200 ms to alert participants that the trial was about to start.…”
Section: Continuous Flash Suppression Tasksupporting
confidence: 69%
See 2 more Smart Citations
“…This has been shown to be the optimal temporal frequency for suppression in other CFS studies (Drewes et al, 2018;Zhu, Drewes, & Melcher, 2016), but is actually a slower rate than Cohen et al (2015), who used ~117 ms (8.5 Hz); nevertheless we found comparable breakthrough times (see Experiment 3). A trial started with the presentation of the black fixation dot for 250 ms which then turned red for 200 ms to alert participants that the trial was about to start.…”
Section: Continuous Flash Suppression Tasksupporting
confidence: 69%
“…A further image characteristic that could influence breakthrough times is the amount of edges (local clustering of contrast changes). In fact, it has previously been suggested that the amount of edges could determine CFS because increased spatial density of Mondrian masks result in longer breakthrough times (Drewes, Zhu, & Melcher, 2018). However, in this previous study, their manipulation of spatial density changed both edge content and global spatial frequency content, contrast and luminance.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…A new mask image was shown every ;167 ms (6 Hz). This has been shown to be the optimal temporal frequency for suppression in other CFS studies (Drewes et al, 2018;Zhu, Drewes, & Melcher, 2016) but is actually a slower rate than Cohen et al (2015), who used ;117 ms (8.5 Hz); nevertheless, we found comparable breakthrough times (see Experiment 3). Before each trial, a black fixation dot was presented for 250 ms, which then turned red for 200 ms to alert participants that the trial was about to start.…”
Section: Cfs Tasksupporting
confidence: 67%
“…A further category-specific image characteristic that could influence breakthrough times is the amount of edges (local clustering of contrast changes). In fact, it has previously been suggested that the amount of edges could determine CFS because increased spatial density of Mondrian masks result in longer breakthrough times (Drewes, Zhu, & Melcher, 2018). However, in this previous study, the manipulation of spatial density changed both edge content and global spatial frequency content, contrast, and luminance.…”
Section: Introductioncontrasting
confidence: 57%